BEYOND PLAY: SYSTEMATIC INSIGHTS INTO GAMIFYING EDUCATION ACROSS PEDAGOGICAL, PERSONAL, AND GAMIFICATION DIMENSIONS - Gur, Duygu; Turel, Yalin Kilic (Anadolu Univ, 2025)
Different variables such as motivation, achievement, and engagement have been investigated in studies on gamification in the field of educational technologies. However, the obtained results differ, which emphasizes the need for studies based on concrete findings related to current trends and needs. In this study, we aim to reveal current research trends regarding gamification in education, identify current research needs, and make suggestions to guide future research through our systematic review. Instead of presenting limited results linked to a certain education level, learning environment, or variable, we share the results of research undertaken at all education levels and digital learning settings collectively and by categorizing (pedagogical, personal, and gamification) all the variables examined. One of the important results of the research is that gamification can be an alternative for solving the problems regarding motivation and participation in distance education. In conclusion, we provide practical suggestions for educators and instructional designers on how to apply gamified learning environments.
Keywords: Gamification; education; gamified learning environments; instructional technologies; systematic review